(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
Empowering employees becomes a current issue as leadership approach as well as a managerial means of contemporary approaches. Empowering employees is predicted to impact on self- efficacy positively. In the first phase of the study, the investigation of validity and reliability of empowering leadership and self-efficacy scale were conducted among healthcare employees in Turkey. In the second phase, the relationships between empowering leadership and the sub- dimension of empowering leadership and self-efficacy were searched. The related scales were performed among 550 healthcare employees, who were selected randomly from 7 different hospitals of states that in different regions of Turkey. Empowering leadership scale of Amundsen and Martinsen (2014), and General Self-efficacy scale of Chen, Gully and Eden (2001) were used to measure designed model within the study. As the results of the study, a new version of empowering leadership scale, which is consisted of 2 dimensions and 5 questions in each dimensions and has reliability and validity in Turkish, was reached. Moreover, a new self- efficacy scale that is insisted of one dimension and 4 questions and has reliability and validity in Turkish was obtained within the analyses. Empowering leadership as total score, sub-dimension of empowering leadership as autonomy and development supportaffects on self-efficacy positively.